Analysis of Verbal Pattern Sentence Children with Autism - Masithah Mahsa; Fabio Testy Ariance; Sumarlam Sumarlam (Unipdu Jombang, 2019)
In this paper discusses about one of the difficulties with language in autistic children that is in the use of sentence patterns orally. The purpose of this study was to determine the form of oral sentence patterns used or possessed by children with autism. Sources of data in this study is autistic children in the SDLP Cangakan Karanganyar with data’s in the form of speech or verbal language. Data collection techniques used in this study is a method of speech and methods of listened. Then, an advanced technique used is the technique of recording and written. Data analysis techniques performed by following three stages, namely: (1) data reduction phase, (2) the stage presentation of data, and (3) stages of inference or verification. Oral forms of sentence patterns of autistic children generally simple or quick-factly, and oral language skills of children with autism depends on the level of autism suffered.Keywords: children with autism, the oral sentence patterns.